CERRADO CONNECTION: MATOPIBA AND ITS ENVIRONMENTAL IMPACTS - Carneiro Ferreira, Edinaiane (Journal of Interdisciplinary Debates, 2023)
Research carried out over two years on deforestation in the Cerrado addresses agricultural expansion in the MATOPIBA region. The objectives are to analyze the environmental impacts and present geoprocessed analyzes for a more sustainable management of the biome. The proposed methodology includes literature review and data analysis.